Metal‐Enhanced Circularly Polarized Luminescence of Self‐Assembled Au@SiO2 Triangular Nanoprisms and Fluorophores in Chiral Cellulose Nanocrystal Films. Issue 20 (27th July 2021) - Zhao, Sixiang; Yu, Yingying; Zhang, Boyu; Feng, Pu; Dang, Congcong; Li, Ming; Zhao, Liancheng; Gao, Liming
Abstract: Amplification of the intensity and dissymmetry factors ( g lum ) of circularly polarized light is desired to broaden the range of applications of circularly polarized luminescence (CPL) because of the small g lum values commonly observed for CPL materials and the loss of intensity resulting from circular polarization. In this study, enhanced CPL produced by metal‐enhanced fluorescence is successfully achieved by the self‐assembly of Au@SiO2 triangular nanoprisms (Au@SiO2 TNPs) and fluorophores (sulforhodamine 101 and methylene blue) in chiral cellulose nanocrystal films. By overlapping the plasmon bands of Au@SiO2 TNPs and the excitation–emission spectra of fluorophores, both the fluorescence intensity and g lum value of CPL are significantly enhanced. For sulforhodamine 101 in the metal‐enhanced CPL system, a 52‐fold fluorescence enhancement is achieved, and the g lum value increased from −0.038 to −0.126. For methylene blue in the metal‐enhanced CPL system, a 201‐fold enhancement of fluorescence is obtained, and the g lum value is enhanced from −0.055 to −0.085. This metal‐enhanced CPL film is expected to generate superior circularly polarized light for extensive CPL applications because of its outstanding enhanced CPL, fluorescence amplification, and feasibility for different fluorophores. Abstract : This study aims to amplify the intensity and dissymmetry factors of circularly polarized luminescence (CPL) in self‐assembled chiral cellulose nanocrystals using the metal‐enhanced fluorescence effect. This study also provides metal‐enhanced CPL films with high enhancement capability and broad applicability. It is believed that these metal‐enhanced CPL films will be a starting point for further research on CPL emission materials and CPL‐based photoelectric devices.